A case of extreme skeletal class III Malocclusion beyond the envelope of discrepancy, managed effectively by a modified ortho-surgical protocol. (June 2021) - Jeyaraj, Priya; Juneja, Pankaj
Abstract: Correction of severe anteroposterior skeletal discrepancy, as described in this case of Extreme Skeletal Class III Malocclusion, can be challenging and fraught with difficulties. Conventional, single stage Bi-jaw Orthognathic surgery, with pre-and post-surgical orthodontics is associated with drawbacks such as risk of relapse and an unsatisfactory outcome, with persisting occlusal discrepancies and skeletal abnormalities, especially when the magnitude of skeletal correction is large. Excessive mandibular setback restricts tongue space, narrows the posterior airway and pharyngeal spaces, and is prone to relapse from the forward pterygomasseteric pull; while large maxillary advancements are accompanied by wound dehiscence, bone exposure and delayed union at the site of pterygomaxillary disjunction, and risk of relapse due to backward palatopharyngeal pull. Bi-jaw surgeries invariably involve considerable blood loss and prolonged operating time with its attendant anaesthetic risks. These drawbacks may be obviated by employing a two staged protocol of Bi-jaw surgeries allowing a minimum time period of 3 months to elapse between them, which allows the oral and maxillofacial musculature to adapt itself to the new jaw position following the first surgery, thus creating a better and more stable environment for the succeeding one. This reduces the chance of relapse thereafter, and produces more effective and stable long term results. The intervening time period also allows for observation of the repositioned jaw and arch relations achieved, and scrutiny for any positional changes in this post-surgical phase, which thereby allows modifications in the planned surgery of the next jaw, thereby achieving the most ideal final outcome.